2012
DOI: 10.1007/s00423-012-0931-y
|View full text |Cite
|
Sign up to set email alerts
|

Is simultaneous splenectomy an additive risk factor in surgical treatment for active endocarditis?

Abstract: Simultaneous valve surgery and splenectomy is an approach for active endocarditis complicated by splenic lesions with a low 180-day mortality. Despite the expected risk elevation by septic lesions and the additive trauma of a laparotomy, patients with simultaneous splenectomy had a favourable outcome regarding early mortality and mortality at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
15
0
2
Order By: Relevance
“…Current indications for splenectomy in patients with splenic emboli include splenic infarction or abscess larger than 2 cm, persistent sepsis symptoms, peripheral lesions, and a ruptured spleen . However, the timing of splenectomy is controversial . Splenectomy concomitant with cardiac surgery increases the duration of surgery and operative insult .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current indications for splenectomy in patients with splenic emboli include splenic infarction or abscess larger than 2 cm, persistent sepsis symptoms, peripheral lesions, and a ruptured spleen . However, the timing of splenectomy is controversial . Splenectomy concomitant with cardiac surgery increases the duration of surgery and operative insult .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe illness (shortness of breath, cough, weight loss, enlarged spleen, and a heart murmur) underwent early splenectomy and others had splenectomy with or following their valve surgery. However, there is no consensus about optimal timing and order of operations . IIA was confirmed by brain angiography and neurological intervention was performed before valve surgery for patients with ruptured, symptomatic, or enlarging IIA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rzadziej splenektomię i zabieg kardiochirurgiczny wykonuje się jednocześnie. U pacjentów obciążonych wysokim ryzykiem operacyjnym alternatywę może stanowić drenaż przezskórny [274,275].…”
Section: Powikłania Dotyczące śLedzionyunclassified
“…Currently there are two proposed therapeutic approaches, one suggesting valve replacement followed by antibiotic therapy associated with close follow-up with CT scans of the abdomen, and the other favoring both splenectomy and valve operation either simultaneously or in a staged fashion [1,2,4]. It must, however, be considered that splenic abscesses may contribute to dissemination of the infection, being prone to sudden rupture, which at times may be fatal [1,2,5]. Robinson et al [6] observed 100% mortality at follow-up in patients with IE without splenectomy and 82% survival in those with splenectomy, emphasizing that removal of the spleen has a positive impact on reducing the risk of graft infection.…”
Section: Commentmentioning
confidence: 97%